Local Structure of Sodium- and Iron-deintercalated NaFeAs - Cassidy, S; Ramos, S; Clarke, S (Wiley, 2014)
The local structures around Fe and As were probed using X-ray absorption spectroscopy in metastable derivatives of NaFeAs obtained by deintercalation of the metals with iodine in THF at room temperature. The deintercalated product with a defective ThCr2Si2 structure is unattainable through conventional high temperature routes due to the size-mismatch between the eight-coordinate site and the Na+ radius in the ThCr2Si2 structure type, and is poorly crystalline. X-ray absorption Near Edge Structure (XANES) measurements show a shift of the Fe K-edge consistent with oxidation of iron to the +3 oxidation state. Changes to the features in the XANES at the As K-edge and analysis of the Extended X-ray Absorption Fine Structure (EXAFS) data from both Fe and As K-edges show that the local structures of Fe and As may only be modelled adequately using a highly defective ThCr2Si2 structural model. This shows that deintercalation of both Na and Fe from NaFeAs occurs to produce NaFe1.7As2, which shares local structural features with the related iron selenides K0.8Fe1.6Se2.